Effects of a school-based intervention on 24-hour movement behaviors in adolescents: A quasi-experimental study - Jaminson Raul Ricardo-Sejin; Carlos Mario Arango-Paternina; Fredy Alonso Patiño-Villada (PLoS ONE, 2025)
Interest in integrating 24-hour movement behaviors (sleep, physical activity, and screen time) has increased in recent years, supporting global guidelines that emphasize their relevance for adolescent health. However, there remains a need for studies that assess the effectiveness of interventions aimed at improving these behaviors. This study aimed to evaluate the effectiveness of a school-based intervention grounded in Self-Determination Theory on: (1) 24-hour movement behaviors; (2) adherence to 24-hour movement behaviors recommendations; (3) health-related quality of life; and (4) Self-Determination Theory constructs associated with 24-hour movement behaviors. A quasi-experimental design with experimental and control groups was conducted, including pre-test, post-test, and follow-up assessments. The study involved 82 adolescents aged 14–17 from two conveniently selected schools in the city of Bello, Colombia. The 12-week intervention included educational, family, and extracurricular components. Effectiveness was analyzed using mixed models and relative risk. The results revealed significant effects of the intervention on screen time (weekdays: F (4.68, 156)=2, p = .01; weekend: F (5.51, 156)=2, p = .005; total week: F (6.32, 156)=2, p = .002) and sleep (weekend: F (6.09, 156)= 2, p = .003; total week: F (3.88, 156)=, p = .02). A significant increase in meeting the weakday sleep recommendation was observed in the experimental group (RR: 1.85, IC95% 1.05–3.25), along with improvements in the Self-Determination Theory constructs of competence and relatedness in physical activity. The intervention demonstrated partial effectiveness, achieving improvements in screen time and sleep. This study contributes to the understanding of the design and implementation of educational interventions targeting 24-hour movement behaviors. Future research should refine the integration of motivational strategies to improve physical activity and overall adherence to recommendations, while also exploring the scalability and sustainability of these school-based interventions.